Castro Alves em busca do cântico dos cânticos - Naves, Reginaldo Vieira (2021)
This dissertation aims to examine the intertextuality between the Song of Songs of Solomon, the Bible's book written by King Salomon, with the poem “Hebreia” (1870), written by Castro Alves (1847-1871). In order to do that, metaphors, synesthesias and symbologies are explored in accordance with the requirements of a research. The first pages consider King Solomon's peculiarities, such as his wisdom, wealth, and culture. An analysis of Sulamita, his lover, and her gifts will follow. The traditions, controversies, and poetry in the Song of Songs are studied in accordance with the understanding of allegorical and literal interpretations. The intertextuality between Brazilian poetry and the Song of Songs of Solomon is highlighted in a narrow survey of prestigious names from different Brazilian Literary Schools. These prestigious authors wove their verses with threads borrowed from the verses of the Biblical Poem since the Romanticism to Cordel literature. When dealing with the Song of Songs’ texts poured into the lines and between the lines of the Hebrew poem, this research’s last pages deal with the Poet Castro Alves's mastery in handling the structure, symbologies, metaphors and synesthesias in favor of the remarkable intertextuality between the Song of Songs, and other biblical passages. This walk with the romantic poet in his search for texts in the Song of Songs gives the reader an opportunity to see up close the beaty of “Hebreia.” The beaty that led the poet to look to the Bible for inspiration to win the “beautiful Jewess” who took his heart on Brazilian soil.